2004
DOI: 10.1210/jc.2003-030666
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Endocrine Effects of a Polyunsaturated Fatty Acid-Rich Diet in Polycystic Ovary Syndrome

Abstract: Effects of a polyunsaturated fatty acid (PUFA)-rich diet were investigated in 17 polycystic ovary syndrome (PCOS) patients. After a 3-month habitual diet period, dietary fats were partly replaced with PUFAs for another 3 months. The PUFA-rich diet increased plasma linoleic acid from 28.36 +/- 1.00% to 33.76 +/- 1.08% (P < 0.002) and alpha-linolenic acid from 0.52 +/- 0.03% to 1.06 +/- 0.10% (P < 0.0001). Fasting glucose increased from 76 +/- 3 to 95 +/- 3 mg/dl (4.2 +/- 0.2 to 5.30.2 mmol/liter; P < 0.0001), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
2
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 31 publications
3
49
2
6
Order By: Relevance
“…Previously we have shown that walnuts increased plasma glucose without changing insulin in PCOS (Kasim- Karakas et al, 2004). However, weight has decreased in this study.…”
Section: Dietary Fatty Acids and Pcos S Kalgaonkar Et Alcontrasting
confidence: 57%
See 1 more Smart Citation
“…Previously we have shown that walnuts increased plasma glucose without changing insulin in PCOS (Kasim- Karakas et al, 2004). However, weight has decreased in this study.…”
Section: Dietary Fatty Acids and Pcos S Kalgaonkar Et Alcontrasting
confidence: 57%
“…Although 46 g almonds or 36 g walnuts each contain 31 g oil, their compositions differ: 31 g of almond-oil delivers 2.4 g saturated fat, 19.5 g MUFA, 7.5 g linoleic acid (LA; 18:2 n-6) and no a-linolenic acid (ALA; 18:3 n-3; Abbate et al, 1996) whereas 31 g walnutoil delivers 2.9 g saturated fat, 4.5 g MUFA, 19.2 g LA and 4.3 g ALA. The fat exchange was accomplished as described previously (Kasim- Karakas et al, 2004). Amount of nut intake was based on average daily energy intake, which was assessed using 7-day food records (Food Processor SQL software; ESHA Research, Salem, OR, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Omega-3 may increase high density lipoprotein cholesterol (HDL), but it may decrease the triglyceride levels. In the women with PCOS, omega-3 can modify the adiponectin (a soluble matrix protein) level, insulin resistance, and lipid profiles (33,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in male rats saturated fatty acids were more prone to accumulate in cells and to increase androgen levels than polyunsaturated fatty acid (PUFA), and to a lesser extent than MUFA [86]. Accordingly, a prospective study found that after a 3-month habitual diet, partly replacing fat by PUFAs for another 3 months improved glucose homeostasis, plasma lipids and sex steroids in women with PCOS [130]. A cross-over study comparing eucaloric diets either enriched with MUFA or low in carbohydrates (CHO), evidenced that both interventions lowered fasting insulin levels and circulating triglycerides, but the acute insulin response to glucose was lower following the low CHO diet relative to the MUFA diet [131].…”
Section: Weight Loss and Exercisementioning
confidence: 99%